Optical tomography system based on charge-coupled device linear image sensors: Particle size measurement - Idroas, M.; Ruzairi, Abdul Rahim; Mohd Hafiz, Fazalul Rahiman; Ibrahim, M. N. (Elsevier B.V, 2011)
Link to publisher's homepage at http://www.elsevier.com/